Permen Sambal Pecel: A New Variant of Traditional Cuisine from Madiun City - Rendy Kurniaji; Vinsensius Widdy Tri Prasetyo; Chatarina Dian Indrawati (Universitas Muhammadiyah Sidoarjo, 2023)
Sambal pecel is a typical food of the City of Madiun. In an effort to maintain the existence and product development, product development needs to be done through variation of sambal pecel products. This study aims to provide an alternative variation of a new product in the form of sambal pecel candy. This new variant of the sambal pecel product is intended to introduce sambal pecel to children. Determination of the formulation for making sambal pecel candy, namely sambal pecel, sucrose, glucose, and water was carried out using an experimental method. In processing the data, researchers used the Design Expert 13 application with the Simplex Lattice Design method. This study gave the result that the form of sambal pecel candy that children like is the lollipop form. Based on the experiment as a whole, the sambal pecel candy formula has a significant effect on organoleptic testing on the hedonic scale value p <0.05. The composition of the pecel sauce chosen by consumers was 25 gr, 80 gr sucrose, 40 gr glucose, and 95 ml water with an average score of 3.89. Highlights: Product Diversification: The study focuses on diversifying traditional sambal pecel into a new product, sambal pecel candy, to attract a wider audience. Child-friendly Introduction: The new candy variant aims to introduce the flavors of sambal pecel to children, promoting the traditional cuisine in a form suitable for young palates. Formulation Experimentation: Through experimental methods and design software, the optimal formulation for sambal pecel candy was determined, considering factors like taste and texture. Keywords: Sambal Pecel Candy, Product Variation, Children, Formulation, Organoleptic Testing